A novel therapeutic approach to treat Alzheimer's disease: The brain‐specific signal peptide peptidase‐like 2b (SPPL2b). (1st February 2022) - Tambaro, Simone; Riccardo, Maccioni; Zerial, Stefania; Wagener, Annika; Andrade‐Talavera, Yuniesky; Fisahn, André; Mentrup, Torben; Schröder, Bernd; Nilsson, Per
Abstract: Background: Alzheimer's disease (AD) is a multifactorial disorder in which the abnormal brain production of amyloid β‐peptide (Aβ) plays a crucial role in its onset. Identifying new mechanisms and proteins involved in AD pathogenesis is critical to finding novel effective disease‐altering therapeutic targets. The intramembrane enzyme Signal Peptide Peptidase Like 2b (SPPL2b), which belongs to the same protein family as presenilin, is a new potential target since it is involved in the proteolysis of two AD‐related proteins: TNF‐alpha and BRI2 involved in the inflammatory response and Aβ production respectively. Here we have investigated for the expression levels and the pathogenic role of SPPL2b in AD. Method: The pathophysiological role of SPPL2b in Aβ metabolism was evaluated in vitro by using human cell lines SH‐SY5Y and HEK293 stably expressing APP, in acute brain slices from WT mice, in brains of a new APP knock‐in AD mouse model ( App NL‐G‐F ) and humans post mortem AD brain tissues. Result: APP overexpression in SH‐SY5Y cells increased SPPL2b expression, which was paralleled by reduced BRI2 levels. A reduction in Aβ40 production was observed in SH‐SY5Y cells after inhibiting SPPL2b activity. In brain slices maintained ex vivo, Aβ42 exposure induced a strong upregulation of SPPL2b. Increased levels of SPPL2b were also observed in the cortex in the early stage of the AD‐associated Aβ pathology of 3 months old App NL‐G‐F . On the contrary, a lower SPPL2b expression was observed in 10 months old App NL‐G‐F mice, when Aβ pathology is severe and accompanied by neuroinflammation, and similarly decreased in humans AD post mortem cortex. Furthermore, immunofluorescence staining showed that SPPL2b is expressed in neurons and glia deposited in the amyloid plaque, indicating a direct role of SPPL2b in Aβ plaques formation. Conclusion: These results strongly support the involvement of SPPL2b in AD pathology, and most important Aβ42 is directly involved in SPPL2b expression. Modulation of the SPPL2b activity, could be potentially beneficial in preventing both Aβ neurotoxicity and neuroinflammation. The brain‐specificity and the few substrates related make of SPPL2b an attractive therapeutic target.